Acrotonia da brotação de macieira em região de inverno ameno - Patto, Leonardo Silva (2017)
During dormancy, temperate plants temporarily stops visible growth. In apple trees, it is known that temperature is the environmental factor that most influences dormancy. The plant requires low temperatures to induce input and then to output endodormancy, thus resumption vegetative grow. It is known that when there isn’t sufficient chilling accumulation, plants present erratic growth, with budbreak occurring predominantly in the distal portion of the branches, compromising the satisfactory budbreak. However, there is little information on the metabolism of these carbohydrates and their relationship to plant dormancy in subtropical humid climates. This work aimed to evaluate the biological and biochemical differences between the distal and proximal portions of apple tree branches that influence acrotonia. From April to October of 2012, 2013 and 2014, branches and spurs of three apple cultivars (Eva, Galaxy and Fuji Suprema) were harvested in a commercial orchard in Palmas-PR. In order to evaluate the dormancy intensity in vegetative and floral buds, single bud cuttings test and Tabuenca test were carried out, respectively. Biochemical variables were also evaluated such as soluble protein content; Alpha-amylase activity; Soluble sugars (glucose, fructose, sucrose and sorbitol); Starch and water content. In general, the cultivars showed the Mean Time to Budbrst (MTB) lower than in temperate climate. The budburst percentage remained high in most of the observation dates for the three cultivars. The Tabuenca test confirmed the precocity of the cultivar Eva and showed very similar behavior between 'Galaxy' and 'Fuji Suprema'. In addition, a very short interval between the endodormancy output under forcing conditions and in field condition was observed. The water content varied according to the temperature pattern in each year, and in 2013, the year of greatest cold accumulation, the lowest values for all cultivars were observed. In 2013, the trend of increased alpha-amylase activity and protein content coincided with the lower value of MTB. Glucose and fructose presented very similar behavior among themselves during the observations. The sucrose content varied from year to year and did not present a fixed pattern. Sorbitol, sugar most abundant in the xylem, tends to be more constant during dormancy with a slight reduction tendency close to budding. The starch content tends to decrease with the first chilling accumulations, however it often undergoes resynthesis due to the heat waves common in winter. There are differences between the distal and proximal portions of the branches for all variables analyzed, with carbohydrate content, enzymatic activity, proteins and humidity predominantly larger in the distal portion of the branches, with some occasional exceptions. This may be associated with the occurrence of acrotonia in apple trees. The evaluated apple trees do not appear to fall into deep endodormancy in a mild winter condition, their metabolism seems to be very subject to temperature oscillations. Plant metabolism tends to change from year to year according to the winter pattern in each year.